2022
DOI: 10.1007/s41347-022-00275-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Young Millennials’ Motivations for Grieving Death Through Social Media

Abstract: Past research has explored social media grief; however, the motivations for using a range of social media sites, specifically by young millennials, to grieve death fail to be explored expansively in existing thanatology research. Fourteen young millennials participated in individual semi-structured interviews, specifically questioning their motivations for using social media sites to grieve. The interviews were analysed using the thematic analysis framework identified by Braun and Clarke (2013). Four themes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…This result would be consistent with the hypothesis that social media is modifying the way new generations are mourning and commemorating the memory of their loved ones. Recently, King & Carter [ 34 ] performed a qualitative study of fourteen bereaved young millennials. The authors found that the participants gave great importance to social media for mourning.…”
Section: Discussionmentioning
confidence: 99%
“…This result would be consistent with the hypothesis that social media is modifying the way new generations are mourning and commemorating the memory of their loved ones. Recently, King & Carter [ 34 ] performed a qualitative study of fourteen bereaved young millennials. The authors found that the participants gave great importance to social media for mourning.…”
Section: Discussionmentioning
confidence: 99%